ナンキョク オングルトウ フキン ノ パドル ノ スイシツ - 南, 英一; ミナミ, エイイチ; 松本, 利松; マツモト, トシマツ; 小坂, 丈予; オサカ, ジョウヨ; MINAMI, Eiiti; MATUMOTO, Tosimatu; OSSAKA, Joyo (国立極地研究所, 1961)
P(論文) Chemical analyses on the water collected in January-February 1957 from 8 puddles on the fast ice near Ongul Island showed the results as seen in Table 2 and led us to the following considerations. The remarkable lower value of the salinity in comparison with sea water means naturally that the puddles were formed by remelting of ice bed, and the remarkable local variation in the salt contents denies the consideration if these puddles should be in reciprocal communication under the surface ice sheet. Of course, the fact, that the relative proportions of the elements contained in puddle waters are quite similar to these of the sea water, tells that the former has got the influence from the latter. But, in details, the equivalent ratios calculated show sufficient differences from that of mean sea waters. This comes from the fractionation in the path of transportation of sea water into puddles, and the stability of the contents through the transportation is in an ascending order as SO_4<Cl≦Na<K, Mg<Ca. This order presents the similarity rather to that of the pond water on East Ongul Island investigated by Ken SUGAWARA than to that of the waters in Japan. The results of investigation on deutrium content indicate that the puddle waters lies between the pond water in East Ongul Island and the nearby sea water in its value. departmental bulletin paper